Proton‐Exchange Rates on Hydroxide Bridges of Mineral‐Like Metal‐Hydroxide Clusters. Issue 6 (29th April 2016) - Fields, Caitlyn R.; Oliveri, Anna F.; Colla, Christopher A.; Johnson, Darren W.; Casey, William H.
Abstract: Soluble metal‐hydroxide clusters of Group 13 metals are popular in both materials chemistry and geochemistry. In geochemistry these clusters are used as experimental models for clay‐like minerals. In materials chemistry these clusters are the precursors for useful thin films. However, little is known about the formation mechanisms and solution dynamics of these species or how they compare to monomer ions. In this study we use 1 H‐NMR spectroscopy to estimate the exchange rates of protons on sites in the Ga13 (μ3 ‐OH)6 (μ2 ‐OH)18 (H2 O)24 (NO3 )15 (Ga13 ) and Ga7 In6 (μ3 ‐OH)6 (μ2 ‐OH)18 (H2 O)24 (NO3 )15 (Ga7 In6 ) cluster species. To date, these clusters provide the best molecular‐scale models for the surface chemistry of thin films and layered minerals. Trivalent metal‐hydroxide minerals are environmentally important, because of the rich acid‐base chemistry that exists in the pH regions of most soils. Our data suggest millisecond timescales for the exchange of protons on the μ2 ‐OH bridges with bulk water in Group 13 metal‐hydroxide minerals, such as tsumgallite and diaspore. Abstract : Soluble metal‐hydroxide clusters of Group 13 metals are popular in both materials chemistry and geochemistry. However, little is known about the formation mechanisms and solution dynamics of these species or how these processes compare to monomer ions. In this study we use 1 H‐NMR spectroscopy to estimate the exchange rates of protons on sites in the Ga13 and Ga7 In6 cluster species.